The Positions of the Magnetic Poles - Jones, Harold Spencer (Polar Record, 1948)
A knowledge of the positions of the magnetic poles is important for the construction of magnetic charts of the polar areas. Charts giving the isogonals, or lines of equal declination, are needed for the purpose of air navigation over the polar regions, which is likely to become of increasing importance. The isogonals have a particularly complicated shape in the polar regions, because both the geographical pole and the magnetic pole are points of singularity, through which all the isogonals necessarily pass.